1988
DOI: 10.1063/1.455324
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of methyl chemisorption on Ni(111)

Abstract: Calculations including electron correlation have been performed for methyl adsorbed on nickel clusters mimicking the Ni(111) surface. The chemisorption energies are evaluated following a recently developed scheme, in which the cluster is prepared for bonding. In this way cluster dependent oscillations of the chemisorption energies are largely eliminated. By also using calculated vibrational frequencies of the adsorbed methyl an almost certain assignment of the preferred chemisorption site is obtained. Methyl i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
31
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 31 publications
7
31
0
Order By: Relevance
“…A softening of these modes during adsorption has been found. 6 It has been explained as due to charge donation from the surface Table II. into the methyl group, 14 or alternatively by a displacement of the methyl radical away from the hollow site that brings one H atom into a Ni atop position. 15 Thus we are left with 9 degrees of freedom of the H-CH 3 dimer, that may be decomposed into three translations, three rotations, and three orientations of the CH 3 radical relative to the C-H bond.…”
Section: E Normal Modes At the Transition Statementioning
confidence: 99%
See 2 more Smart Citations
“…A softening of these modes during adsorption has been found. 6 It has been explained as due to charge donation from the surface Table II. into the methyl group, 14 or alternatively by a displacement of the methyl radical away from the hollow site that brings one H atom into a Ni atop position. 15 Thus we are left with 9 degrees of freedom of the H-CH 3 dimer, that may be decomposed into three translations, three rotations, and three orientations of the CH 3 radical relative to the C-H bond.…”
Section: E Normal Modes At the Transition Statementioning
confidence: 99%
“…14,15 The carbon atom is located 1.56 Å above the surface. Again, this bond distance is somewhat lower than the result of 1.84 Å from CI cluster calculations.…”
Section: Ch 3 On Ni(111)mentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22][23][24][25][26] Yang and Whitten 15,26 have reported that the adsorption energy of CH 3 on the Ni(111) surface using the many-electron embedding theory and modeling the lattice as a 28-atom, three-layer cluster. Ab initio CI cluster calculation was performed by Schule and coworkers 16 on Ni(111) with distinct cluster sizes. The extended Hückel method was widely employed, such as the chemisorption studies of hydrocarbons by Gavin et al 17 on Ni(111), methyl adsorption on Pt(111) by Minot et al, 18 and the bonding and coupling of CH x on Co, Cr, and Ti by Hoffmann and coworks.…”
mentioning
confidence: 99%
“…13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Among them, most studies were concentrated on Ni(111). [15][16][17][18][19][20][21][22][23][24][25][26] Yang and Whitten 15,26 have reported that the adsorption energy of CH 3 on the Ni(111) surface using the many-electron embedding theory and modeling the lattice as a 28-atom, three-layer cluster. Ab initio CI cluster calculation was performed by Schule and coworkers 16 on Ni(111) with distinct cluster sizes.…”
mentioning
confidence: 99%